EphB4 and ephrin-B1 expression in the intra-testicular-resident macrophages in mice. (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The objective was to find out the expression of EphB4 receptor and ephrin-B1 ligand by the macrophages that live inside the mouse testicles. Materials and Methods: Messenger ribonucleic acid (mRNA) expression of EphB4 and ephrin-B1 was identified via RT-PCR amplification, and protein expression was examined by immunostaining. Results: Analysis using RT-PCR revealed that mRNA of EphB4 and ephrin-B1 were noticed in the examined testis of all postnatal ages. Furthermore, immunostaining revealed that F4/80-positive intra-testicular-resident macrophages were located in the intertubular spaces within the testis and more densely around the intra-testicular excurrent duct system, and increased in number gradually during the postnatal period of development until 5 weeks of age, when the mice attain their maturity (puberty), and maintained thereafter. Both EphB4 and ephrin-B1 immunoreactivity were noticed in F4/80-positive intra-testicular-resident macrophages within the testis of all studied postnatal ages. Ephrin-B1 and EphB4 immunoreactivity were weak during early postnatal development until the age of 2 weeks, and then ephrin-B1 immunoreactivity became very strong and EphB4 immunoreactivity became strong at the age of 3 weeks, and they continued to do so until the age of 8 weeks. Furthermore, EphB4 receptor was tyrosine-phosphorylated in testis. Conclusion: The expression of EphB4 and ephrin-B1 in mice intra-testicular-resident macrophages is being examined for the first time in this work. The localization of EphB4 and ephrin-B1, and EphB4 tyrosine-phosphorylation suggest that EphB4/ephrin-B1 signaling might occur in the intra-testicular-resident macrophages, and may participate in maintaining male fertility.J. Adv. Vet. Anim. Res., 11(3): 746-753, September 2024http://doi.org/10.5455/javar.2024.k826